Evaluation of the Teaching Recovery Techniques intervention among newcomer students in Swedish schools: a randomised controlled trial turned into a feasibility study - Natalie Durbeej; Raziye Salari; Anna Sarkadi; Reeta Kankaanpä; Ilse Derluyn; An Verelst; Fatumo Osman (BMC, 2024)
Abstract Background During recent years, Europe has faced the arrival of migrants whereof a considerable group of youth present mental health problems, such as symptoms of post-traumatic stress disorder (PTSD). Schools offer a safe environment for mental health interventions to these groups, yet there is limited research on the impact of school-based interventions addressing mental health problems in newcomer youths, especially in the Swedish context. This cluster randomized controlled trial (RCT) aimed to explore the effectiveness of the Teaching Recovery Techniques (TRT) intervention among newcomer students with PTSD symptoms in Swedish secondary schools. Methods Nine schools were randomly assigned to TRT or a wait list control group prior to the baseline assessment. Follow-up data were collected immediately following the intervention and three months post-intervention. In total, 531 students were approached, of which 61 gave consent and were eligible to be included in the study: 55 in TRT and 6 in the control condition. Given the low number of participants in the control condition, we merely analyzed students who had received TRT. Results We report on feasibility of recruitment, data collection, intervention delivery and intervention effectiveness. In terms of intervention effectiveness, within subjects ANOVAs revealed significant reductions in PTSD symptoms and general mental health problems from baseline to the three months-follow-up (p < 0.001). Conclusions Our results indicate that TRT is a promising school-based intervention for newcomer students with PTSD symptoms. For a successful implementation of TRT in the school context, schools need to be engaged and the implementation should be managed by a local coordinator. Trial registration ISRCTN, ISRCTN48178969, Retrospectively registered 20/12/2019.